S7 Single-centre 14-year retrospective analysis of patients with post-thoracoscopy diagnosis of non-specific pleuritis. (11th November 2022) - Mohammad, S; Li, D; Vella, C; Tufail, M; Sudhir, R; Panchal, RK
Abstract : Introduction and Objectives: Nonspecific pleuritis (NSP) is defined as a fibrinous or inflammatory pleuritis with an incidence of up to 30% following medical thoracoscopy (MT). 5–25% of patients with NSP subsequently develop malignancy. This study aims to compare the characteristics of patients diagnosed with NSP who had a benign disease (BD) course with those who developed malignant disease (MD). Methods: A retrospective analysis was conducted of 596 MT performed at a regional pleural centre from January 2006 - June 2020 to allow for 2 years follow-up. Data on age, gender, smoking history, asbestos exposure, history of malignancy, CT findings, co-morbidities and subsequent malignancy was collected from electronic medical records. Results: NSP was diagnosed in 120/596 patients (20%). 10 patients were excluded due to incomplete data. Both BD & MD groups had similar demographics including age, sex, smoking history and asbestos exposure (see table 1 ). The median follow-up for all cases was 17.5 months. 15.5% (17/110) patients developed MD during the course of their follow-up. The median time course for diagnosing MD was 21 days. Pre-thoracoscopy CT findings of lung parenchymal nodules/masses (MD 5/17 v BD 4/93, p-value 0.01) and pleural nodularity (MD 4/17 v BD 3/93, p-value 0.001) reached statistical significance for subsequently developing malignancy. The MD group were more likely to have further invasive procedures than the BD group (MD 9/17 v BD 18/93, p-value 0.05) with a median time to procedure of 24 days (MD 15 v BD 34). Further procedures in the BD group concluded a benign aetiology. VATS was the next most common procedure undertaken. In the MD group mesothelioma was the most common malignancy (35%). In the BD group the most common co-morbidities were cardiovascular (49%) and endocrine (26%). Conclusion: Majority of NSP cases follow a benign course but a significant proportion develop malignancy. Pre-thoracoscopy CT findings are important in identifying this cohort and require closer monitoring. In patients with a high pre-test probability further investigation for malignancy should not be delayed. Reference: Janssen J, Maldonado F, Metintas M. What is the significance of non-specific pleuritis? A trick question. Clin Respir J 2018;12 (9):2407–2410. doi:10.1111/crj.12940